2012
DOI: 10.1186/1746-1596-7-76
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal lymphomas in a North American population: clinicopathologic features from one major Central-Midwestern United States tertiary care medical center

Abstract: BackgroundGastrointestinal (GI) lymphomas are very common types of extranodal lymphomas, and we hypothesize there are regional differences in subtype, distribution in the GI tract, and epidemiological features among the different populations.MethodsWe retrospectively evaluated the clinical, molecular and histologic features of North American primary and secondary GI lymphomas diagnosed from 2000–2009 seen at our institution. We utilized immunohistochemistry and fluorescence in situ hybridization to further eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 46 publications
1
26
0
Order By: Relevance
“…Regarding North American countries, 2 related studies were performed in the USA and Canada, using 216 and 149 cases, respectively. The results showed that the average age was 61 and 63.8 years, and that the gender ratio was 1.7: 1 and 1.5: 1, respectively [3,18,19] . The gender ratio of this study was similar to that of North American countries and lower than that in India.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Regarding North American countries, 2 related studies were performed in the USA and Canada, using 216 and 149 cases, respectively. The results showed that the average age was 61 and 63.8 years, and that the gender ratio was 1.7: 1 and 1.5: 1, respectively [3,18,19] . The gender ratio of this study was similar to that of North American countries and lower than that in India.…”
Section: Discussionmentioning
confidence: 91%
“…For instance, the small intestine was the second most commonly affected site in the research of Warrick et al [19] . The ileocecum region was defined as the section from the terminal of the ileum to the cecum, because of the ambiguity of anatomic classification, the designation for this region was different among previous studies, which has caused the different frequencies of affected small intestinal lymphoma and large intestinal lymphoma [3,18,19] . Thus, in the current study, we isolated this section as an independent area, belonging to neither the small nor the large intestine.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations